ANALISIS MOTIVASI PEGAWAI PADA PELABUHAN PERIKANAN NUSANTARA KARANGANTU, PROVINSI BANTEN - Armansyah, Mohamad; Hidayat, Yahya Rahmana (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractThis research is an of evaluation on employee motivation at Fishery Port of Nusantara (PPN) inKarangantu, Banten Province, as a Technical Implementation Unit of the Directorate General of Capture Fishery, Ministry of Marine Affairs and Fisheries. This study was conducted to determine the factors that most influence employee motivation based on 3 independent variables tested, namely: remuneration, organizational culture, and leadership. While the data collection procedure is conducted through a survey of all employees, where employees are given a questionnaire in a closed model. To obtain valid and reliable data, tested on samples in research instrument that is processed by using SPSS 21. From the results of data processing obtained value coefficient of determination (R2) of 0.667 or 66.7%. The data gathered can be interpreted as: work motivation of 66.7 percent is influenced by remuneration, organizational culture, and leadership. While the remaining 33.3 percent is explained by other independent variables that are not included in this study. This research suggests that to improve employee motivation, it is necessary to formulate a change of policy concerning organizational culture by evaluating the human resource placement pattern, in accordance with the competence of educational background, in order to carry out the tasks according to the direction of the leader, to work professionally and to provide the best service to the stakeholders.Ã‚Â Keywords: remuneration, organizational culture, leadershipÃ‚Â AbstrakPenelitian ini merupakan salah satu evaluasi atas motivasi pegawai yang diterapkan pada Pelabuhan Perikanan Nusantara (PPN) Karangantu, Provinsi Banten, selaku Unit Pelaksana Teknis Direktorat Jenderal Perikanan Tangkap, Kementerian Kelautan dan Perikanan. Penelitian ini dilakukan untuk mengetahui faktor-faktor yang paling mempengaruhi motivasi pegawai berdasarkan 3 variabel independen yang diuji, yaitu: remunerasi, budaya organisasi dan kepemimpinan. Sementara prosedur pengumpulan data dilakukan melalui survey terhadap seluruh karyawan, di mana karyawan diberikan kuesioner dengan model tertutup. Untuk mendapatkan data yang valid dan terpercaya, dilakukan uji pada sampel pada instrument penelitian yang diolah dengan menggunakan SPSS 21. Dari hasil pengolahan data diperoleh nilai koefisien determinasi (R2) sebesar 0,667 atau 66,7%. Dapat diartikan motivasi kerja sebesar 66,7 persen dipengaruhi oleh remunerasi, budaya organisasi, dan kepemimpinan. Sedangkan sisanya 33,3 persen dijelaskan oleh variabel independen lain yang tidak dimasukan dalam penelitian ini. Penelitian ini menyarankan bahwa untuk meningkatkan motivasi pegawai perlu merumuskan perubahan kebijakan mengenai Budaya Organisasi dengan mengevaluasi pola penempatan sumber daya manusia, sesuai dengan kompetensi latar belakang pendidikan, agar dapat menjalankan tugas sesuai arahan pimpinan, bekerja secara professional dan dapat memberikan pelayanan terbaik kepada stakeholders.Ã‚Â Kata kunci: remunerasi, budaya organisasi, kepemimpinan